PERCEPTIONS OF THE PEOPLE RECRUITED ABOUT THE STRATEGIC ACTION “O BRASIL CONTA COMIGO” (BRAZIL COUNTS ON ME) - Cunha, Inara Pereira da; Moraes, Sílvia Helena Mendonça de; Pereira, Ewângela Aparecida; Oshiro, Maria de Lourdes; Assis, André Vinicius Batista de; Pessalacia, Juliana Dias Reis; Nascimento, Débora Dupas Gonçalves do (Cogitare Enfermagem, 2022)
Objective: to analyze the perceptions of academics and supervisors about the strategic action “O Brasil Conta Comigo”(Brazil counts on me). Method: cross-sectional study conducted in Mato Grosso do Sul - Brazil, from December 2020 to March 2021, in two stages: 1) Exploratory (quantitative), via analysis of reports of the 33 supervisors and 90 academics convened, application of an online questionnaire; 2) In-depth (qualitative), using the remote focus group technique, with convenience sampling. Descriptive and content analysis was performed. Results: the reasons for joining and remaining with the action (scholarship, internship hours, and social responsibility), the pedagogical aspects (training, evaluation, and support from educational institutions, and management), and the contributions of the action (assistance and professional training) were identified. Conclusion: the general perceptions of the recruits are positive. Pedagogical aspects related to the evaluation of academics and support from higher education institutions should be reviewed, for more assertive actions in times of health crisis.